'Clinical Chatter': every nurse informed. Issue 9 (12th March 2017) - Talbott, Carolyn; Watson, Lynn; Tariman, Joseph; Sorenson, Matthew
Abstract : Aims and objectives: To assess the acceptability and usability of a standardised communication tool for nurses. Background and significance: Communication is key in health care. On a daily, if not hourly, basis, nursing staff is inundated with new information regarding tools and resources, practice changes and the work environment. However, there is currently no standardised messaging or delivery method to effectively communicate new information. Even with a plethora of communication tools such as flyers, posters, emails, unit huddles and unit meetings, there is no means to guarantee attendance to crucial information. Design: Descriptive, cross‐sectional online survey, implemented at a nonacademic, suburban hospital with 280 nurses. Methods: The Clinical Chatter, an online tool developed by nursing leadership to standardise messages regarding the organisation, new tools and resources, professional development, recognition and unit updates, was delivered to each nurse on a weekly basis followed by administration of Acceptability and Usability scales. Results: The Clinical Chatter tool has adequate acceptability and usability as a method of communication among nurses in a hospital organisation. Sociodemographic variables of age and years of experience had no statistically significant association with perceived acceptance and usefulness of the tool. Conclusion: The findings indicate that the Clinical Chatter tool can be used as a standardised communication tool to deliver key information among nurses working in a hospital organisation. Nursing leadership must establish and support a clear communication system to enhance patient care and outcomes and improve nursing job satisfaction. Relevance to clinical practice: Communication is vital to advancing health care. Lack of communication among nursing has been linked to unsafe patient care: medication errors, unhealthy work environments and decreased nurse retention rates. Clinical Chatter is an effective communication tool for presentation of institutional information to nursing personnel.